How Does Residential Property Market React to Flood Risk in Flood-Prone Regions? A Case Study in Nagoya City - Inoue, Ryo; Hatori, Kohei (Frontiers in Water, 2021)
To quantify the flood risk awareness of real estate market participants and residents, previous studies analyzed the effect of flood risks on residential property values. However, most studies focused on the impact of recent flood events and the publication of new flood risk information; the behavior in flood-prone regions in which repeated damages occurred and lessons learned consequently has not been the focus of analysis. Moreover, there is a growing national concern in Japan about an increase in future flood risks due to climate change, although their effect on property values has not been discussed. In this study, we analyzed residential property values in Nagoya City (Aichi Prefecture, Japan), a megacity that has experienced significant flood damage in major historical and recent floods. The main objective of this study is to determine the effects of past and recent flood experiences and the increasing concerns about flood risks on recent residential property values. The results revealed that historical flood damage had the largest impact on residential property values in Nagoya City, and devaluation increased due to growing concerns about natural disasters in Japan. The disclosure of flood risk information also had an impact on property values, increasing devaluation after disclosure. On the contrary, the occurrence of recent floods did not have an impact on property values, suggesting that flood risk awareness had already been strong in the target area. These findings are different from those of many previous studies. The observed trends in residential property values in the target area are likely a characteristic response in flood-prone regions, where flood risk awareness is enhanced due to repeated flood damage.